Sodium Hypochlorite dosage for rainwater harvesting system for potable use in Gambang, Malaysia - Qasim, Ban; Abdul Syukor, Abd Razak; Siddique, Md. Nurul Islam (2017)
Rainwater harvesting system for potable use is essential in many parts around the world from the aspects of both sustainable water supply and public health.